Biologi Reproduksi Ikan Kiper, Scatophagus argus (Linnaeus, 1766) di Teluk Pabean, Indramayu - Emmanuel - Manangkalangi; Lenny S. Syafei; Ida Lapadi; Paskalina T. Lefaan; Nurhani Widiastuti; M. Fadjar Rahardjo (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
The spotted scat, Scatophagus argus (Linnaeus, 1766) is a component of the estuarine ecosystem with little reproductive information. Therefore, this study was conducted with the aim of describing aspects of the reproductive biology of this fish species through sex ratio, size at first sexual maturity, and spawning season. The collection of fish samples from the waters of Pabean Bay was carried out every month between January and December 2015. The fishing gear used were sero and gill nets. A total of 428 individuals were collected consisting of larval, juvenile, pre-adult, and adult stages. The ratio of the number of male and female individuals is relatively balanced (1.00 : 1.05). The size of the male individual's first sexual maturity at a total length of 102.95 mm and 112.44 mm in female individuals. The composition of gonadal maturity level and gonadal maturity index value indicated that there was reproductive activity that lasted throughout the year and increased in January-February and September-November. Information on reproductive aspects obtained in this study can be used as a basis for the management of this fish resource, including through recommendations for closing locations and fishing times.